2000
DOI: 10.1002/j.1556-6676.2000.tb02577.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational and Vocational Aspirations of Minority and Female Students: A Longitudinal Study

Abstract: This study examined the relative importance of school, family, personal/psychological, race, and sex variables in predicting educational and vocational aspirations. A nationally representative sample of 10th-grade students was followed through 2 years beyond their high school. Results suggested that sex and race significantly predicted educational and vocational aspirations of students. The educational aspiration model was shown to be more robust than the occupational aspiration model. Overall, students showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
209
4
13

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(263 citation statements)
references
References 37 publications
(68 reference statements)
29
209
4
13
Order By: Relevance
“…Contrary to other studies (Karraker 1992;Mau and Bikos 2000;Wilson and Wilson 1992), we do not find students who identify as a race or ethnicity other than White to have higher educational expectations than those who identify as White. In our results, there are no statistically significant differences between the educational aspirations of White youth and Black youth.…”
Section: Other Factors Related To Educational Expectationscontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to other studies (Karraker 1992;Mau and Bikos 2000;Wilson and Wilson 1992), we do not find students who identify as a race or ethnicity other than White to have higher educational expectations than those who identify as White. In our results, there are no statistically significant differences between the educational aspirations of White youth and Black youth.…”
Section: Other Factors Related To Educational Expectationscontrasting
confidence: 99%
“…Racial/ethnic minorities have greater net aspirations than do Whites (Karraker 1992;Mau and Bikos 2000;Qian and Blair 1999). One explanation for this pattern is that parents in minority families may be especially encouraging of their children to strive for higher education and success because they themselves are more likely to have experienced disadvantage and discrimination in their own lives (Wilson and Wilson 1992).…”
Section: Racial/ethnic Minority Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, feared selves often consist of the negative stereotypes attributed to ones ethnic group, such as becoming a manual laborer for Hispanic American youths. In line with these prevailing stereotypes, a study of ethnic groups in the USA found that Asian American youths report the highest educational and occupational aspirations while Hispanic Americans report the lowest (Mau & Bikos, 2000). In contrast to these findings, another recent study found no support for difference in reported aspirations and expectations between American ethnic minority groups.…”
Section: Ethnicitymentioning
confidence: 95%
“…Conversely, boys rate social status (Ander-man & Anderman, 1999), becoming successful (Nurmi et al, 1999) and financial aspirations as more important (Kasser & Ryan, 1993). In the area of schooling, girls report and endorse educational goals to a greater extent than boys (Honora, 2002;Marjoribanks, 2002a;Mau & Bikos, 2000;Nurmi, 1994;Nurmi et al, 1995;Yowell, 2000). A disproportionate number of girls are found to endorse possible academic selves in arts and humanities compared to boys who endorse more academic possible selves in business and mathematics (Lips, 2004).…”
Section: Processesmentioning
confidence: 99%